YAP induziert chromosomale Instabilität in Leberkrebspatienten = YAP induces chromosomal instability in liver cancer patients - Weiler, Sofia Maria Elisabeth (Der Pathologe, 2018)
Background: The Hippo/YAP signaling pathway is a central regulator of organ growth and cell proliferation. Activation of the transcriptional co-activator and oncogene YAP (yes-associated protein) supports the development of liver cancer. Aims: The aim of this work was to analyze the molecular mechanisms which are responsible for YAP-induced hepatocarcinogenesis. Methods: YAP was silenced using siRNAs in liver cancer cell lines and effects on target gene expression were analyzed via real-time polymerase chain reaction (PCR) and western immunoblotting. Immunoprecipitation and chromatin immunoprecipitation was used to study interacting proteins and binding to target gene promoter regions, respectively. Transgenic mice with liver-specific and inducible YAP expression were used for in vivo analysis. Gene expression data from hepatocellular carcinoma (HCC) patients were used to analyze YAP-dependent gene signatures and to correlate with clinical data. HCC tissue microarrays were analyzed using immunohistochemistry. Results: Together with the transcription factors TEAD4 and FOXM1, YAP induces the expression of genes which are responsible for the development of chromosomal instability (CIN). The overexpression of these CIN genes characterizes liver cancer patients with a poor prognosis. Mechanistically, YAP/TEAD4 and FOXM1 bind to the promoter regions of the CIN genes to directly regulate their expression. The treatment of YAP-transgenic mice with a specific FOXM1 inhibitor reduces the YAP-dependent hepatomegaly, CIN gene expression and CIN. The analysis of human HCC tissue samples confirms the statistical correlation between YAP, FOXM1 and CIN. Discussion: These results reveal a new oncogenic mechanism of the Hippo/YAP signaling pathway and identify YAP and FOXM1 as potential targets for targeted therapies.
Gesehen am 03.07.2019